α- Glucosidase inhibition, antioxidant and cytotoxicity activities of semi-ethanolic extracts of Bridellia ferruginea benth. and Ceiba pentandra L. Gaerth from Benin - BOTHON, FIFA THEOMAINE DIANE; Debiton, Eric; Hounnakpon Yedomonhan, Hounnakpon; AVLESSI, FÉLICIEN; Teulade, Jean-Claude; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2012)
The use of plant extracts in the treatment of human disease requires a definition of optimal conditions. This study objective is to evaluate the inhibition capacity of α-glucosidase activity of Bridelia ferruginea benth bark and Ceiba pentandra L. Gaerth root semi-ethanolic extracts compared to acarbose. Their antioxidant activity were also tested by three techniques: 2,2diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, Ferric reducing antioxidant power (FRAP) and the Oxygen Radical Absorbance Capacity (ORAC). Results indicated that these extracts have antioxidant property and α-Glucosidase inhibitory activity (IC50 = 1.4 ± 0.04 µg / mL for B. ferruginea and 51 ± 0.7 µg / mL for C. pentandra) higher than the reference compound acarbose (IC50 = 726 ± 15 mg / mL). Bridelia ferruginea extract was the most active of the two. In vitro cytotoxicity evaluation of the extracts was done by fluorometric assay: Resazurin reduction test on human fibroblast primary culture have showed a very low toxicity. Bridelia ferruginea and Ceiba pentandra The semi-ethanolic extracts could therefore constitute a credible alternative to replace the expensive synthetic drugs in the treatment of diabetes.
Keywords: Bridelia ferruginea; Ceiba pentandra; α-glucosidase; antioxidant; cytotoxicity